Effects of Brand Awareness, Brand Association, Perceived Quality, and Brand Loyalty on Overall Brand Equity in Sport. A Case Study of an Amateur Football Sports Club - Bańbuła Joanna (Sciendo, 2024)
The primary objective of this research endeavor outlined in the thesis was to evaluate the impact of the individual dimensions of Customer-Based Brand Equity (CBBE) - brand awareness, brand association, perceived quality and brand loyalty - on the overall brand capital of the researched amateur football club Talent Warszawa. The author sought to discern which among the individual dimensions of CBBE exerted the most significant influence on fostering the overall brand capital of the club under examination. A questionnaire was distributed amongst the constituents of Talent Warszawa, including players, parents and guardians, players' families, and supporters of amateur football. The survey garnered responses from a total of 102 stakeholders affiliated with the club. The reliability of the measurement scale was validated through Cronbach's Alpha analysis.